Gender Analysis of Farmers from the Perspective of Food Security: A Case Study of Owan West Local Government Area of Edo State, Nigeria - L E Ilevbaoje (Journal of Agricultural Extension, 2015)
This paper examines how three classes of farmers, namely, food -secured, medium food -secured and food -insecured, discriminate with selected variables. Analyses of the data obtained indicate that about 51.7 %, 30% and 18.3% of farmers in Owan Local Government Area are food -insecure, medium food -secure and food -secure, respectively. It was also observed that food -secured farmers cultivate high -value crops such as cocoa, rice, yams (Dioscorea rotundata), have larger farm sizes, operate longer fallow periods and have the capacity to cultivate all their own land. On the other hand, food -insecured farmers own smaller farm holdings, harvest the bounties of nature, notably, volunteer vegetables - Corchorus olitorius, Talinum trianqulare, etc. In addition, the food -insecure group operate shorter fallow periods due to limited land holdings. The medium food -secure farmers lie between these two extremes - food secure and foo- insecure groups. In order to remedy the plight of these rural poor, the paper recommends their inclusion in the nation's special programme for Food Security and the need to serve them through extension delivery.